2020
DOI: 10.1007/s00170-020-06203-y
|View full text |Cite
|
Sign up to set email alerts
|

Ecofriendly inclined drilling of carbon fiber-reinforced polymers (CFRP)

Abstract: Key composite made aerostructures such as fuselage inner walls, flap support fairings, empennage ribs, and the vertical fin ribs are comprised of non-vertical inclined and radial holes that join with other key metallic and non-metallic structures. Carbon fiber reinforced plastics (CFRP) are also used in the aerospace, automotive, marine, and sports-related applications due to their superior properties such as high strength to weight ratio, better fatigue, and high stiffness. CFRP drilling operation is differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The increase in thrust force observed for both CFRP and Al during dry drilling using uncoated tools may due to high wear [103]. In compressed air environment, lowest thrust forces were found (1.46 times) for 30°inclination as compared to dry cutting in drilling of CFRP reported by Parvez et al (2020) [104]. Cryogenic fluid between-the-holes shows favorable results with respect to drilling of CFRP concerning hole quality, thrust force and energy consumption while a reduction in surface roughness and energy consumption in case of drilling of titanium alloy [105].…”
Section: Drilling Of Carbon-fiber-reinforced-plastics (Cfrp) and Meta...mentioning
confidence: 89%
“…The increase in thrust force observed for both CFRP and Al during dry drilling using uncoated tools may due to high wear [103]. In compressed air environment, lowest thrust forces were found (1.46 times) for 30°inclination as compared to dry cutting in drilling of CFRP reported by Parvez et al (2020) [104]. Cryogenic fluid between-the-holes shows favorable results with respect to drilling of CFRP concerning hole quality, thrust force and energy consumption while a reduction in surface roughness and energy consumption in case of drilling of titanium alloy [105].…”
Section: Drilling Of Carbon-fiber-reinforced-plastics (Cfrp) and Meta...mentioning
confidence: 89%
“…The lubrication mechanism of MQL is analyzed, that is, the pressurized directional transportation of oil mist makes oil droplets that penetrate into the pore network on the workpiece and grinding wheel effectively. The G-ratio of MQL grinding is 115.38% higher than that of dry grinding [188]. Pervaiz et al [189] found different rules and believed that the MQL strategy in external configuration could not provide favorable performance.…”
Section: Minimum Quantity Lubricationmentioning
confidence: 99%
“…However, 1%vol SWCNT + MQL has the optimal effect on improving the surface roughness of CFRP and Al composites. Table 3 [30,100,154,156,162,187,188,191,207,208,210,211] lists the processing results of different MQL conditions and dry processing.…”
Section: Minimum Quantity Lubricationmentioning
confidence: 99%
“…Carbon fiber-reinforced polymer (CFRP) laminates are a new type of composite material that are extensively applied in aerospace, manufacturing, military industries and other high-tech fields due to their high specific strength, relative thermal stability, and low weight. [1][2][3] However, in aircraft CFRP structures, barely visible impact damage (BVID) may easily occur while facing complicated harsh environments with impacts such as hail strikes, lightning strikes, and tool drops. BVID is a kind of damage that originates inside the material, without significant signs on the surface of the structure.…”
Section: Introductionmentioning
confidence: 99%